Optical laminate and display device

CN113740952BActive Publication Date: 2026-10-27SUMITOMO CHEM CO LTD
View PDF 21 Cites 0 Cited by

Patent Information

Application Number
CN202110583829.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-11-26
Filing Date
2021-05-27
Publication Date
2026-10-27
Estimated Expiration
2041-05-27

AI Technical Summary

Benefits of technology

[0038]根据本发明,可以提供一种光学层叠体,是包含偏振元件的光学层叠体,其适合于车载用的显示装置,湿热耐久性及高温耐久性优异,并可以提供使用了该光学层叠体的显示装置及该光学层叠体的制造方法。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113740952B_ABST
    Figure CN113740952B_ABST
Patent Text Reader

Abstract

The present application provides an optical laminate, which is an optical laminate including a polarizing element, suitable for a display device for vehicle use, and excellent in humidity and heat durability and high-temperature durability. The optical laminate of the present application is an optical laminate having a polarizing element and an antireflection film, the water content of the polarizing element being equal to or higher than the equilibrium water content at a temperature of 20°C and a relative humidity of 20% and equal to or lower than the equilibrium water content at a temperature of 20°C and a relative humidity of 48%, and further, the optical laminate satisfying at least one of the following requirement (i) and the following requirement (ii): (i) the moisture permeability of the antireflection film at a temperature of 40°C and a relative humidity of 90% being 20 g / m 2 ·day or less; and (ii) having a protective film having a moisture permeability at a temperature of 40°C and a relative humidity of 90% of 20 g / m 2 ·day or less between the polarizing element and the antireflection film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to optical laminates, display devices, and methods for manufacturing optical laminates. Background Technology

[0002] Liquid crystal displays (LCDs) are not only used in LCD televisions, but also widely used in personal computers, mobile devices such as mobile phones, and in-vehicle applications such as car navigation systems. Typically, an LCD device has a liquid crystal panel component with polarizing plates containing polarizing elements bonded to both sides of the liquid crystal display unit using an adhesive layer. The display is achieved by controlling the light from a backlight component using the liquid crystal panel component.

[0003] In addition, in recent years, organic EL displays have been widely used, just like liquid crystal displays, in televisions, mobile devices such as mobile phones, and automotive applications such as car navigation systems. In organic EL displays, in order to suppress the reflection of external light at the metal electrode (cathode) and thus prevent it from appearing as a mirror, a circular polarizing plate (a laminate containing polarizing elements and a λ / 4 plate, sometimes simply referred to as a polarizing plate) is sometimes placed on the visible side surface of the organic EL display unit.

[0004] As mentioned above, polarizing plates are increasingly being used in vehicles as components of liquid crystal displays and organic EL displays. Compared to polarizing plates used in other mobile devices such as televisions and mobile phones, polarizing plates used in automotive displays are frequently exposed to humid and hot environments, requiring high-temperature and high-humidity durability.

[0005] On the other hand, in-vehicle display devices require touch panel functionality when used for purposes such as car navigation. In recent years, the ratio of on-cell and in-cell touch panels has increased. In this application, since the polarizing plate on the visible side is located on the outermost surface, in addition to the aforementioned durability, anti-reflective glare functionality is also required.

[0006] Japanese Patent Application Publication No. 2011-081219 (Patent Document 1) discloses a scheme for using an anti-glare hard coating film consisting of a multi-layered anti-reflective layer formed by sputtering, which is stacked on an anti-glare layer for the purpose of preventing glare from reflected external light (Example 1, etc.).

[0007] Existing technical documents

[0008] Patent documents

[0009] Patent Document 1: Japanese Patent Application Publication No. 2011-081219 Summary of the Invention

[0010] The problem that the invention aims to solve

[0011] The present invention provides an optical laminate containing polarizing elements, which is suitable for automotive display devices and has excellent damp heat durability and high temperature durability. The present invention also provides a display device using the optical laminate and a method for manufacturing the optical laminate.

[0012] means for solving problems

[0013] The present invention provides the following optical laminate, display device and method for manufacturing optical laminate.

[0014] [1] An optical laminate, comprising a polarizing element and an anti-reflective film,

[0015] The moisture content of the polarizing element is above the equilibrium moisture content at 20°C and 20% relative humidity, and below the equilibrium moisture content at 20°C and 48% relative humidity.

[0016] At least one of the following requirements (i) and (ii) must be satisfied:

[0017] (i) The antireflective film has a temperature of 40°C, a relative humidity of 90%, and a moisture permeability of 20 g / m³. 2 Below the heavens;

[0018] (ii) Between the polarizing element and the antireflective film, there is a temperature of 40°C and a relative humidity of 90%, with a permeability of 20 g / m². 2 • A protective film below the sky.

[0019] [2] An optical laminate, which is an optical laminate having a polarizing element and an anti-reflective film,

[0020] The moisture content of the optical laminate is above the equilibrium moisture content at 20°C and 20% relative humidity, and below the equilibrium moisture content at 20°C and 48% relative humidity.

[0021] At least one of the following requirements (i) and (ii) must be satisfied:

[0022] (i) The antireflective film has a temperature of 40°C, a relative humidity of 90%, and a moisture permeability of 20 g / m³. 2 Below the heavens;

[0023] (ii) Between the polarizing element and the antireflective film, there is a temperature of 40°C and a relative humidity of 90%, with a permeability of 20 g / m². 2 • A protective film below the sky.

[0024] [3] An optical laminate as described in [1] or [2], wherein a protective film is provided between the polarizing element and the antireflective film.

[0025] [4] An optical laminate according to any one of [1] to [3], wherein the antireflective film comprises a substrate film and an antireflective layer disposed on the surface of the substrate film.

[0026] The antireflective layer comprises multiple thin films with different refractive indices.

[0027] [5] According to the optical laminate described in [4], the antireflective layer comprises a thin film with silicon dioxide (SiO2) as the main component.

[0028] [6] According to the optical laminate described in [4] or [5], wherein the antireflective layer comprises a thin film with niobium pentoxide (Nb2O5) or titanium dioxide (TiO2) as the main component.

[0029] [7] An optical laminate according to any one of [4] to [6], wherein the thickness of the antireflective layer is 100 nm to 350 nm.

[0030] [8] An optical laminate according to any one of [4] to [7], wherein the antireflective film further comprises a hard coating disposed between the substrate film and the antireflective layer.

[0031] [9] A display device having a display unit and an optical laminate as described in any one of [1] to [8],

[0032] The optical laminate is stacked on the visible side surface of the display unit in such a way that the polarizing element and the anti-reflective film are arranged sequentially from the display unit side.

[0033]

[10] A method for manufacturing an optical laminate, which is the method for manufacturing an optical laminate described in [1].

[0034] The manufacturing method includes a moisture content adjustment step, which adjusts the moisture content of the polarizing element to a level above the equilibrium moisture content of 20°C and 20% relative humidity and below the equilibrium moisture content of 48% relative humidity at 20°C.

[0035]

[11] A method for manufacturing an optical laminate is the method for manufacturing an optical laminate described in [2].

[0036] The manufacturing method includes a moisture content adjustment step, which adjusts the moisture content of the optical laminate to a level above the equilibrium moisture content of 20°C and 20% relative humidity and below the equilibrium moisture content of 48% relative humidity at 20°C.

[0037] Invention Effects

[0038] According to the present invention, an optical laminate comprising a polarizing element can be provided, which is suitable for automotive display devices, exhibiting excellent resistance to damp heat and high temperature, and a display device using the optical laminate and a method for manufacturing the optical laminate can be provided. Attached Figure Description

[0039] Figure 1 This is an example of a schematic cross-sectional view showing the layered structure of an optical laminate. Detailed Implementation

[0040] [Optical laminate]

[0041] The optical laminate of this invention includes a polarizing element and an anti-reflective film. The anti-reflective film is disposed on the visible side surface of the polarizing element. The optical laminate may have a protective film (hereinafter also referred to as "first protective film") laminated on the surface of the polarizing element on the side of the anti-reflective film, or it may have a protective film (hereinafter also referred to as "second protective film") laminated on the surface of the polarizing element on the side opposite to the anti-reflective film side. In this specification, the first protective film is defined as a protective film laminated between the polarizing element and the anti-reflective film. Furthermore, in this specification, the term "polarizing plate," when it includes a polarizing element and has a first protective film and / or a second protective film attached to the polarizing element, refers to the laminate containing them.

[0042] Figure 1 This is an example of a schematic cross-sectional view showing the layer structure of the optical laminate of this embodiment. The optical laminate 100 includes a polarizing element 10 and an anti-reflective film 20, and also includes a first protective film 11 laminated on the surface of the polarizing element 10 on the side of the anti-reflective film 20, and a second protective film 12 laminated on the surface of the polarizing element 10 on the side opposite to the side of the anti-reflective film 20.

[0043] The optical laminate of this embodiment has at least one of the features described in (a) and (b).

[0044] (a) The moisture content of the polarizing element is above the equilibrium moisture content of 20°C and 20% relative humidity, and below the equilibrium moisture content of 48% relative humidity at 20°C.

[0045] (b) The moisture content of the optical laminate is above the equilibrium moisture content of 20°C and 20% relative humidity, and below the equilibrium moisture content of 48% relative humidity at 20°C.

[0046] Regarding (a) above, the moisture content of the polarizing element is preferably an equilibrium moisture content of 30% or higher at a temperature of 20°C and a relative humidity of 45% or lower. More preferably, the moisture content of the polarizing element is an equilibrium moisture content of 30% or higher at a temperature of 20°C and a relative humidity of 40% or lower.

[0047] Regarding (b) above, the moisture content of the optical laminate is preferably an equilibrium moisture content of 30% or higher at a temperature of 20°C and a relative humidity of 45% or lower. More preferably, the moisture content of the optical laminate is an equilibrium moisture content of 30% or higher at a temperature of 20°C and a relative humidity of 40% or lower.

[0048] The optical laminate satisfies at least one of the following requirements (i) and (ii).

[0049] (i) The anti-reflective film has a temperature of 40°C, a relative humidity of 90%, and a moisture permeability of 20 g / m². 2 Below the heavens.

[0050] (ii) A temperature of 40°C and a relative humidity of 90% with a permeability of 20 g / m² is maintained between the polarizing element and the antireflective film. 2 • A protective film below the sky.

[0051] Satisfying the above requirement (ii) means the same as satisfying the following requirement (iia).

[0052] (iia) has a surface layer of antireflective film on the side of the polarizing element, with a moisture permeability of 20 g / m at a temperature of 40°C and a relative humidity of 90%. 2 The first protective film below the sky.

[0053] The optical laminate of this embodiment improves both humid heat durability and high temperature durability by ensuring that the water content of the polarizing element is within the aforementioned range and by satisfying at least one of the aforementioned requirements (i) and (ii). As an optical laminate with excellent humid heat durability, it provides an optical laminate with minimal change in polarization degree before and after placement in a humid heat environment. A humid heat environment is, for example, an environment with a temperature of 85°C and a relative humidity of 85%. The evaluation of humid heat durability can be performed according to the evaluation method described in the embodiments. As an optical laminate with excellent high temperature durability, it provides an optical laminate with minimal change in transmittance before and after placement in a high temperature environment. A high temperature environment is, for example, an environment with a temperature of 95°C. The evaluation of high temperature durability can be performed according to the evaluation method described in the embodiments.

[0054] <Polarization element>

[0055] Polarizing elements can be formed by adsorbing and orienting a layer containing polyvinyl alcohol (hereinafter also referred to as "PVA")-based resin (hereinafter also referred to as "PVA-based resin layer" in this specification). Examples of such polarizing elements include those formed by dyeing a PVA-based resin film with a dichroic pigment and then uniaxially stretching it; and those formed by coating a substrate film with a coating liquid containing PVA-based resin, dyeing the PVA-based resin layer of the laminated film with a dichroic pigment, and then uniaxially stretching the laminated film.

[0056] The polarizing element is formed from a PVA-based resin obtained by saponifying a polyvinyl acetate-based resin.

[0057] In addition to polyvinyl acetate homopolymers, copolymers of vinyl acetate with other monomers that can be copolymerized can also be cited as examples of polyvinyl acetate-based resins. Examples of other monomers that can be copolymerized include unsaturated carboxylic acids, olefins such as ethylene, vinyl ethers, and unsaturated sulfonic acids.

[0058] The degree of saponification of the PVA-based resin is preferably about 85 mol% or more, more preferably about 90 mol% or more, and even more preferably about 99 mol% to 100 mol%. The degree of polymerization of the PVA-based resin is 1000 to 10000, preferably 1500 to 5000. This PVA-based resin can be modified, for example, it can be aldehyde-modified polyvinyl formal, polyvinyl acetal, polyvinyl butyral, etc.

[0059] The thickness of the polarizing element in this embodiment is preferably 5 to 50 μm, more preferably 5 to 30 μm, and even more preferably 8 to 25 μm. By making the thickness of the polarizing element 50 μm or less, the effect of polyolefination of PVA-based resin on the reduction of optical properties can be suppressed under high-temperature conditions. In addition, by making the thickness of the polarizing element 5 μm or more, it is easy to manufacture a configuration that achieves the desired optical properties.

[0060] The transmittance of the visibility correction monomer of the polarization element is preferably 38.8% to 44.8%, more preferably 40.4% to 43.2%, and even more preferably 40.7% to 43.0%. If the transmittance of the visibility correction monomer is greater than 44.8%, the optical properties, such as red discoloration, may deteriorate significantly under high-temperature conditions. If the transmittance of the visibility correction monomer is less than 38.8%, polyolefin formation may be more easily promoted under high-temperature conditions, leading to greater deterioration of optical properties.

[0061] The visibility-corrected single-cell transmittance can be determined by measuring the Y value after visibility correction using a 2-degree field of view (C light source) as specified in JIS Z8701-1982. The visibility-corrected single-cell transmittance can be easily measured, for example, using a spectrophotometer (model: V7100) manufactured by Nippon Spectrophotometer Co., Ltd.

[0062] (Feature(a))

[0063] In the case of feature (a), the moisture content of the polarizing element is at least the equilibrium moisture content of 20% relative humidity at 20°C, and less than or equal to 48% relative humidity at 20°C. Preferably, it is at least the equilibrium moisture content of 30% relative humidity at 20°C, and less than or equal to 45% relative humidity at 20°C. More preferably, it is less than or equal to 42% relative humidity at 20°C, even more preferably, it is less than or equal to 40% relative humidity at 20°C, and most preferably, it is less than or equal to 38% relative humidity at 20°C. If the equilibrium moisture content is less than 20% relative humidity at 20°C, the handleability of the polarizing element decreases, and it is prone to breakage. By having an equilibrium moisture content of less than 48% relative humidity at 20°C, an optical laminate with excellent damp heat durability and high temperature durability can be provided. It can be inferred that if the moisture content of the polarizing element is high, the polyolefination of the PVA-based resin contained in the polarizing element is more easily promoted. The water content of the polarizing element mentioned above refers to the water content of the polarizing element in the optical laminate.

[0064] As a method to confirm whether the moisture content of a polarizing element is above the equilibrium moisture content of 20°C and 20% relative humidity, and below the equilibrium moisture content of 48% relative humidity at 20°C, it can be considered to have reached equilibrium with the environment if it is stored in an environment adjusted to the above temperature and relative humidity range and there is no change in mass over a certain period of time. Alternatively, the equilibrium moisture content of the polarizing element in an environment adjusted to the above temperature and relative humidity range can be calculated in advance, and the moisture content of the polarizing element can be compared with the pre-calculated equilibrium moisture content to confirm this.

[0065] There are no particular limitations on the method for manufacturing a polarizing element with an equilibrium moisture content of 20°C and 20% relative humidity or higher, and an equilibrium moisture content of 48% relative humidity or lower. For example, methods such as storing the polarizing element in an environment adjusted to the above temperature and relative humidity range for 10 minutes or more and 3 hours or less, or heating it at 30°C or higher and 90°C or lower can be cited.

[0066] As another preferred method for manufacturing polarizing elements with the aforementioned moisture content, examples include storing a laminate in which a protective film is deposited on at least one side of the polarizing element, or a laminate composed of polarizing elements, in an environment adjusted to the aforementioned temperature and relative humidity range for 10 minutes to 120 hours; or performing heat treatment at 30°C to 90°C. Another example is that, during the manufacture of an image display device, an image display panel in which an optical laminate is deposited on an image display unit is stored in an environment adjusted to the aforementioned temperature and relative humidity range for 10 minutes to 3 hours, or performing heat treatment at 30°C to 90°C.

[0067] Regarding the moisture content of the polarizing element, it is preferable to adjust it as follows: the moisture content is within the aforementioned numerical range during the material stage used to construct the optical laminate, either as a separate polarizing element or as part of a laminate of the polarizing element and protective film. Adjusting the moisture content after constructing the optical laminate results in excessive curling, which can easily lead to undesirable conditions when bonded to the image display unit. By constructing the optical laminate using a polarizing element whose moisture content is adjusted to the aforementioned range during the material stage before constructing the optical laminate, it is easy to construct an optical laminate with a polarizing element whose moisture content meets the aforementioned numerical range. Alternatively, the moisture content of the polarizing element in the optical laminate can be adjusted to the aforementioned numerical range while the optical laminate is bonded to the image display unit. In this case, curling is less likely to occur since the optical laminate is bonded to the image display unit.

[0068] (Feature (b))

[0069] In the case of feature (b), the moisture content of the optical laminate is above the equilibrium moisture content of 20% relative humidity at 20°C, and below the equilibrium moisture content of 48% relative humidity at 20°C. Preferably, it is above the equilibrium moisture content of 30% relative humidity at 20°C, and below the equilibrium moisture content of 45% relative humidity at 20°C. More preferably, it is below the equilibrium moisture content of 42% relative humidity at 20°C, even more preferably, it is below the equilibrium moisture content of 40% relative humidity at 20°C, and most preferably, it is below the equilibrium moisture content of 38% relative humidity at 20°C. If the moisture content of the optical laminate is less than the equilibrium moisture content of 20% relative humidity at 20°C, the workability of the optical laminate decreases, and it is prone to breakage. If the moisture content of the optical laminate is greater than the equilibrium moisture content of 48% relative humidity at 20°C, the transmittance of the polarizing element is prone to decrease. It can be inferred that if the moisture content of the optical laminate is high, the polyolefination of the PVA-based resin is more easily promoted.

[0070] As a method to confirm whether the moisture content of the optical laminate is within the range of equilibrium moisture content above 20°C and 20% relative humidity, and below 48% relative humidity at 20°C, it can be considered to have reached equilibrium with the environment if it is stored in an environment adjusted to the above temperature and relative humidity range and there is no change in mass over a certain period of time. Alternatively, the equilibrium moisture content of the optical laminate in an environment adjusted to the above temperature and relative humidity range can be calculated in advance, and the moisture content of the optical laminate can be compared with the calculated equilibrium moisture content to confirm this.

[0071] There are no particular limitations on the method for manufacturing an optical laminate with an equilibrium moisture content of 20°C and 20% relative humidity or higher, and an equilibrium moisture content of 48% relative humidity or lower. For example, methods such as storing the optical laminate in an environment adjusted to the above temperature and relative humidity range for 10 minutes or more and 3 hours or less, or heating it at 30°C or higher and 90°C or lower can be cited.

[0072] Another method is to heat the image display panel, on which the optical laminate is stacked, during the manufacture of the image display device, in an environment with the temperature and relative humidity adjusted to the above range for 10 minutes to 3 hours or at 30°C to 90°C.

[0073] (Manufacturing method of polarization element)

[0074] There is no particular limitation on the manufacturing method of polarizing elements. Typical methods include: a method of manufacturing by stretching, dyeing, cross-linking, etc., a pre-wound polyvinyl alcohol resin film; and a method of stretching a laminate obtained by coating a polyvinyl alcohol resin-containing coating liquid onto a substrate film to form a polyvinyl alcohol resin layer as a coating layer (hereinafter referred to as "manufacturing method 2").

[0075] Manufacturing method 1 can be carried out by a process of uniaxially stretching a polyvinyl alcohol-based resin film, a process of adsorbing the dichroic pigment by dyeing the polyvinyl alcohol-based resin film with a dichroic pigment such as iodine, a process of treating the polyvinyl alcohol-based resin film with the adsorbed dichroic pigment with a boric acid aqueous solution, and a process of washing with water after treatment with boric acid aqueous solution.

[0076] The swelling process involves immersing a polyvinyl alcohol (PVA) resin film in a swelling bath. This process removes surface contaminants and adhesives from the PVA film and, by swelling, inhibits uneven dyeing. The swelling bath typically uses a water-based medium, such as water, distilled water, or pure water. Surfactants and alcohols can be added to the swelling bath as needed, following standard procedures.

[0077] The temperature of the swelling bath is preferably around 10–60°C, more preferably around 15–45°C, and even more preferably around 18–30°C. Furthermore, the immersion time in the swelling bath cannot be fixed because the degree of swelling of the polyvinyl alcohol-based resin film is affected by the temperature of the swelling bath; however, it is preferably around 5–300 seconds, more preferably around 10–200 seconds, and even more preferably around 20–100 seconds. The swelling process can be performed only once, or multiple times as needed.

[0078] The dyeing process involves immersing a polyvinyl alcohol (PVA) resin film in a dyeing bath (iodine solution). This allows the PVA resin film to adsorb iodine or dichroic dyes and other dichroic substances, causing them to orient. The iodine solution is typically an aqueous solution containing iodine and iodides as a dissolving agent. It should be noted that examples of iodides include potassium iodide, lithium iodide, sodium iodide, zinc iodide, aluminum iodide, lead iodide, copper iodide, barium iodide, calcium iodide, tin iodide, and titanium iodide. Among these, potassium iodide is suitable from the viewpoint of controlling the potassium content in the polarizing element.

[0079] In the staining bath, the concentration of iodine is preferably about 0.01 to 1% by weight, more preferably about 0.02 to 0.5% by weight. In the staining bath, the concentration of iodide is preferably about 0.01 to 10% by weight, more preferably about 0.05 to 5% by weight, and even more preferably about 0.1 to 3% by weight.

[0080] The temperature of the dyeing bath is preferably around 10–50°C, more preferably around 15–45°C, and even more preferably around 18–30°C. Furthermore, the immersion time in the dyeing bath cannot be fixed because the degree of dyeing of the polyvinyl alcohol-based resin film is affected by the temperature of the dyeing bath; however, it is preferably around 10–300 seconds, more preferably around 20–240 seconds. The dyeing process can be performed only once, or multiple times as needed.

[0081] The crosslinking process involves immersing a polyvinyl alcohol (PVA) resin film dyed in the dyeing process into a treatment bath (crosslinking bath) containing a boron compound. The boron compound crosslinks the PVA resin film, allowing iodine molecules or dye molecules to adsorb onto the crosslinked structure. Examples of boron compounds include boric acid, borates, and borax. The crosslinking bath is generally an aqueous solution; however, it can also be a mixture of an organic solvent miscible with water and water. Furthermore, from the viewpoint of controlling the potassium content in the polarizing element, the crosslinking bath preferably contains potassium iodide.

[0082] In the crosslinking bath, the concentration of the boron compound is preferably about 1 to 15% by weight, more preferably about 1.5 to 10% by weight, and even more preferably about 2 to 5% by weight. Furthermore, when potassium iodide is used in the crosslinking bath, the concentration of potassium iodide is preferably about 1 to 15% by weight, more preferably about 1.5 to 10% by weight, and even more preferably about 2 to 5% by weight.

[0083] The temperature of the crosslinking bath is preferably around 20–70°C, more preferably around 30–60°C. Furthermore, the immersion time in the crosslinking bath cannot be fixed because the degree of crosslinking of the polyvinyl alcohol resin film is affected by the temperature of the crosslinking bath; however, it is preferably around 5–300 seconds, more preferably around 10–200 seconds. The crosslinking process can be performed only once, or multiple times as needed.

[0084] The stretching process is a procedure in which a polyvinyl alcohol (PVA) resin film is stretched to a specified ratio in at least one direction. Generally, the PVA resin film is uniaxially stretched along the transport direction (length direction). There are no particular restrictions on the stretching method; either wet stretching or dry stretching can be used. The stretching process can be performed once or multiple times as needed. The stretching process can be performed at any stage of the manufacturing process of the polarizing element.

[0085] The treatment bath (stretching bath) in the wet stretching process can typically be water, or a mixture of water and an organic solvent that is miscible with water. From the viewpoint of controlling the potassium content in the polarization element, the stretching bath preferably contains potassium iodide. When potassium iodide is used in the stretching bath, its concentration is preferably about 1 to 15% by weight, more preferably about 2 to 10% by weight, and even more preferably about 3 to 6% by weight. Furthermore, from the viewpoint of suppressing film breakage during stretching, the treatment bath (stretching bath) may contain a boron compound. In this case, the concentration of the boron compound in the stretching bath is preferably about 1 to 15% by weight, more preferably about 1.5 to 10% by weight, and even more preferably about 2 to 5% by weight.

[0086] The temperature of the stretching bath is preferably around 25–80°C, more preferably around 40–75°C, and even more preferably around 50–70°C. Furthermore, the immersion time in the stretching bath cannot be fixed because the degree of stretching of the polyvinyl alcohol-based resin film is affected by the temperature of the stretching bath; however, it is preferably around 10–800 seconds, more preferably around 30–500 seconds. It should be noted that the stretching treatment in the wet stretching method can be performed together with any one or more of the following processes: swelling, dyeing, cross-linking, and cleaning.

[0087] Examples of dry stretching methods include inter-roll stretching, heated roll stretching, and compression stretching. It should be noted that dry stretching can be performed concurrently with the drying process.

[0088] The total stretch ratio (cumulative stretch ratio) applied to the polyvinyl alcohol-based resin film can be appropriately set according to the purpose, but it is preferably about 2 to 7 times, more preferably about 3 to 6.8 times, and even more preferably about 3.5 to 6.5 times.

[0089] The cleaning process involves immersing the polyvinyl alcohol (PVA) resin film in a cleaning bath to remove foreign matter remaining on the surface of the PVA resin film. The cleaning bath typically uses a water-based medium, such as water, distilled water, or pure water. Furthermore, from the viewpoint of controlling the potassium content in the polarizing element, potassium iodide is preferably used in the cleaning bath. In this case, the concentration of potassium iodide in the cleaning bath is preferably about 1 to 10% by weight, more preferably about 1.5 to 4% by weight, and even more preferably about 1.8 to 3.8% by weight.

[0090] The temperature of the cleaning bath is preferably around 5–50°C, more preferably around 10–40°C, and even more preferably around 15–30°C. Furthermore, the immersion time in the cleaning bath cannot be fixed because the degree of cleaning of the polyvinyl alcohol resin film is affected by the temperature of the cleaning bath; however, it is preferably around 1–100 seconds, more preferably around 2–50 seconds, and even more preferably around 3–20 seconds. The cleaning process can be performed only once, or multiple times as needed.

[0091] The drying process involves drying the polyvinyl alcohol-based resin film, which has been cleaned in the cleaning process, to obtain the polarizing element. Drying can be carried out using any suitable method, such as natural drying, forced-air drying, or heat drying.

[0092] Manufacturing method 2 can be performed through the following steps: applying a coating solution containing the aforementioned polyvinyl alcohol resin onto a substrate film; uniaxially stretching the resulting laminated film; adsorbing the dichroic pigment by dyeing the polyvinyl alcohol resin layer of the uniaxially stretched laminated film with a dichroic pigment; treating the film adsorbed with the dichroic pigment with a boric acid aqueous solution; and washing with water after treatment with the boric acid aqueous solution. The substrate film used to form the polarizing element can also be used as a protective layer for the polarizing element. The substrate film can be peeled off from the polarizing element as needed.

[0093] Anti-reflective film

[0094] The antireflective film has an antireflective function that reduces the reflectivity of light incident from the visible side surface of the optical laminate. The optical laminate incorporates an antireflective film to prevent contrast reduction caused by glare from reflected external light. As an antireflective film, to meet the above requirement (i), a moisture permeability of 20 g / m² under conditions of 40°C and 90% relative humidity can be used. 2 Less than 10 days, preferably 10g / m 2 • Anti-reflective film with a permeability of less than 1000 m². The moisture permeability of the anti-reflective film is measured using the method described in the examples below. By using such an anti-reflective film with low moisture permeability, the durability against damp heat and high temperature can be improved. The moisture permeability of the anti-reflective film can be adjusted by the material and thickness of the anti-reflective layer, the material and thickness of the substrate film, etc. The moisture permeability of the anti-reflective film under conditions of 40°C and 90% relative humidity is typically 1 g / m². 2 More than 10 days.

[0095] An antireflective film can be, for example, an antireflective film having an antireflective layer on one side of a substrate film. There are no particular limitations on the substrate film; a substrate film using the same material as that used in the protective film described later can be used.

[0096] As an anti-reflective film, it can be a known anti-reflective film or a commercially available anti-reflective film, for example, the following anti-reflective films can be cited.

[0097] (a) Antireflective films that utilize the principle of a so-called moth-eye structure, comprising a raised pattern with a period controlled to be below the wavelength of visible light (as described in Japanese Patent Application Publication Nos. 2010-122599, 2001-517319, 2004-205990, 2004-287238, 2001-27505, 2002-286906, and International Publication No. 2006 / 059686). For example, MOSMITE (a registered trademark, manufactured by Mitsubishi Chemical Corporation) can be used as a commercially available product.

[0098] (b) Anti-reflective film containing a fine embossed pattern that performs optical functions (anti-reflective film described in Japanese Patent Application Publication No. 2004-59822, Japanese Patent Publication No. 5-46064, Japanese Patent Publication No. 6-85103, etc.).

[0099] (c) An anti-reflective film comprising a pattern of numerous fine bumps and depressions with spacing below the wavelength of light (anti-reflective film described in Japanese Patent Application Publication No. 2001-264520, Japanese Patent Application Publication No. Hei 9-80205, etc.).

[0100] (d) Antireflective films having single or multiple layers with adjusted refractive indices (as described in Japanese Patent Application Publication Nos. 2000-187102, 2004-345333, etc.). Commercially available products may include, for example, MTAR and MTAGAR (manufactured by Bikan Co., Ltd.).

[0101] The thickness of the antireflective coating is, for example, 10 μm or more and 100 μm or less.

[0102] As an antireflective film, a thin film with strictly controlled thickness and refractive index, or an antireflective film with two or more layers of thin films, is suitable. It should be noted that in this specification, "thin film" refers to a film with a thickness of 1 μm or less. The antireflective layer can be configured such that the phase reversal of the incident and reflected light cancels each other out due to the interference effect of light, thereby achieving antireflective function. The wavelength region of visible light that exhibits antireflective function is, for example, 380–780 nm, particularly the wavelength region with high visibility of 450–650 nm. Preferably, the antireflective layer is designed in a way that minimizes the reflectivity at its center wavelength of 550 nm. The thickness of the antireflective layer is preferably 100 nm–350 nm, more preferably 150 nm–300 nm.

[0103] In the design of antireflective layers based on the interference effect of light, one way to enhance this interference effect is, for example, to increase the refractive index difference between the antireflective layer and the anti-glare hard coating described later. Generally, in multilayer antireflective layers with a structure of 2 to 15 layers of thin films (thickness and refractive index strictly controlled), multiple layers with different refractive indices are formed at a specified thickness. This increases the freedom of optical design for the antireflective layer, further improves the antireflective effect, and makes the spectral reflection characteristics uniform (flat) in the visible light region. Due to the high thickness accuracy required for the thin film, dry methods such as vacuum evaporation, sputtering, and CVD are generally used to form each layer. Sputtering is preferred to ensure that the water transmittance is within a specified range. Furthermore, by using antireflective films formed by sputtering, a highly scratch-resistant optical laminate can be constructed.

[0104] As an anti-reflective layer, it is preferable to use an anti-reflective layer formed by alternating layers of low refractive index and high refractive index. The high refractive index layers or the low refractive index layers may not have the same refractive index, but it is preferable from the viewpoint of suppressing material cost and film formation cost if the same material is used to set the same refractive index.

[0105] Examples of materials that can form a low-refractive-index layer include silicon dioxide (SiO2), silicon oxynitride (SiON), gallium oxide (Ga2O3), aluminum oxide (Al2O3), lanthanum oxide (La2O3), lanthanum fluoride (LaF3), magnesium fluoride (MgF2), and sodium aluminum fluoride (Na3AlF6). Among these, silicon dioxide (SiO2) is the most preferred choice considering its low refractive index, lack of absorption in the visible light region, and high film strength.

[0106] Materials that can constitute a high refractive index layer include niobium pentoxide (Nb₂O₅), titanium dioxide (TiO₂), zirconium dioxide (ZrO₂), tantalum pentoxide (Ta₂O₅), silicon oxynitride (SiON), silicon nitride (Si₃N₄), and niobium silicon oxide (SiNbO). Among these, considering the high refractive index and high film strength, niobium pentoxide (Nb₂O₅) or titanium dioxide (TiO₂) are preferred. Furthermore, to ensure no absorption in the visible light region, niobium pentoxide (Nb₂O₅) is the most preferred.

[0107] By controlling the ratio of constituent elements in any compound to deviate from the stoichiometric ratio, or by controlling the film density during film formation, the refractive index can be varied to some extent. It should be noted that the materials constituting the low-reflectivity layer and the high-reflectivity layer are not limited to the compounds mentioned above, as long as the refractive index condition is met. Additionally, unavoidable impurities may be included.

[0108] An anti-reflective film can have a hard coating layer between the substrate film and the anti-reflective layer. By adding a hard coating layer, the mechanical properties of the anti-reflective layer, such as hardness and elastic modulus, can be improved. Preferably, the hard coating layer has high surface hardness and excellent scratch resistance. For example, the hard coating layer can be formed by coating the substrate film with a solution containing a curable resin.

[0109] Examples of curable resins include thermosetting resins, UV-curing resins, and electron beam curing resins. Types of curable resins include polyester resins, acrylic resins, urethane resins, urethane acrylate resins, amide resins, silicone resins, silicate resins, epoxy resins, melamine resins, oxetane resins, and urethane acrylate resins. One or more of these curable resins can be appropriately selected and used.

[0110] Among these, acrylic resins, urethane acrylate resins, and epoxy resins are preferred for their high hardness, UV curability, and excellent productivity, with urethane acrylate resins being the most preferred. UV-curable resins include UV-curable monomers, oligomers, and polymers. Preferred UV-curable resins include, for example, resins with UV-polymerizable functional groups, and specifically, resins containing acrylic monomers and oligomers having two or more, particularly three to six, of these functional groups.

[0111] To ensure the anti-glare film possesses both anti-glare and anti-reflective properties, a hard coating layer disposed on the surface of the substrate film is preferably anti-glare. Examples of anti-glare hard coatings include hard coatings in which microparticles are dispersed in the aforementioned curable resin matrix. The microparticles dispersed in the resin matrix can be, without particular limitation, cross-linked or non-cross-linked organic microparticles formed from various transparent polymers such as silica, alumina, titanium dioxide, zirconium oxide, calcium oxide, tin oxide, indium oxide, cadmium oxide, and antimony oxide; glass microparticles; polymethyl methacrylate, polystyrene, polyurethane, acrylic-styrene copolymers, benzoguanamine, melamine, and polycarbonate; or transparent microparticles such as silicone microparticles. One or more of these microparticles can be appropriately selected. Among these, microparticles with a refractive index higher than that of the matrix resin are preferred; for example, organic microparticles with a refractive index of 1.5 or higher, such as styrene beads (refractive index 1.59), are preferred. The average particle size is preferably 1 to 10 μm, more preferably 2 to 5 μm. The proportion of particles is not particularly limited, however, it is preferably 6 to 20 parts by weight relative to 100 parts by weight of the matrix resin.

[0112] A hard coating can be formed, for example, by applying a solution containing a curable resin onto a substrate film. A UV polymerization initiator is preferably included in the solution used to form the hard coating. To form an anti-glare hard coating containing microparticles, it is preferable to apply a solution containing the curable resin and the aforementioned microparticles onto a transparent film. The solution may contain additives such as leveling agents, thixotropic agents, and antistatic agents. In the formation of the anti-glare hard coating, by including a thixotropic agent (such as silica or mica with a particle size of 0.1 μm or less) in the solution, a fine textured structure caused by protruding particles can be easily formed on the surface of the hard coating.

[0113] The thickness of the hard coating is not particularly limited; however, to achieve high hardness, it is preferably 0.5 μm or more, more preferably 1 μm or more. Considering the ease of coating formation, the thickness of the hard coating is preferably 15 μm or less, more preferably 12 μm or less, and even more preferably 10 μm or less. Furthermore, to avoid hindering the release of moisture from the polarizing element to the outside, and to maintain a high moisture permeability of the film substrate, the thickness of the hard coating is preferably within the above-mentioned range.

[0114] The arithmetic mean roughness Ra of the surface on the formation side of the antireflective layer of the substrate film is preferably 1.5 nm or less, more preferably 1.0 nm or less. The arithmetic mean roughness Ra can be 0.00 nm or more, or 0.05 nm or more. When a hard coating is formed on the substrate film, the arithmetic mean roughness of the hard coating is the arithmetic mean roughness of the surface on the formation side of the antireflective layer of the substrate film. The arithmetic mean roughness Ra is determined from a 1 μm square observation image obtained using an interatomic force microscope (AFM).

[0115] As described above, if a hard coating is formed by coating, the arithmetic mean roughness of the substrate film surface can be reduced. If the surface of the substrate film is smooth, the arithmetic mean roughness of the surface of the antireflective layer formed thereon also decreases, and the scratch resistance of the antireflective film tends to improve.

[0116] <Protective Film>

[0117] There are no particular limitations on the protective film, but it is preferable to form it from a material with excellent transparency, mechanical strength, thermal stability, water resistance, and stability of phase difference. The material used for the protective film is not particularly limited, and examples include films containing methyl methacrylate resins, polyolefin resins, cyclic olefin resins, polyvinyl chloride resins, cellulose resins, styrene resins, acrylonitrile-butadiene-styrene resins, acrylonitrile-styrene resins, polyvinyl acetate resins, polyvinylidene chloride resins, polyamide resins, polyacetal resins, polycarbonate resins, modified polyphenylene ether resins, polybutylene terephthalate resins, polyethylene terephthalate resins, polysulfone resins, polyethersulfone resins, polyarylate resins, polyamide-imide resins, and polyimide resins.

[0118] These resins can be used alone or in combination of two or more. Additionally, these resins can be used after optional and suitable polymer modification, such as copolymerization, crosslinking, molecular end modification, stereoregularity control, and mixing modifications, including those involving reactions between dissimilar polymers.

[0119] Cellulose-based resins can be organic esters or mixed organic esters of cellulose in which some or all of the hydrogen atoms of the hydroxyl groups are replaced by acetyl, propionyl, and / or butyryl groups. Examples include resins containing cellulose acetates, propionates, butyrates, and mixtures thereof. Among these, triacetylcellulose, diacetylcellulose, cellulose acetate-propionate, and cellulose acetate-butyrate are preferred.

[0120] These resins can be formulated with appropriate additives within a range that does not compromise transparency. Examples of additives include, for instance, antioxidants, UV absorbers, antistatic agents, lubricants, nucleating agents, antifogging agents, antiblocking agents, phase difference reducers, stabilizers, processing aids, plasticizers, impact-resistant additives, matting agents, antibacterial agents, and antifungal agents. Multiple additives can be used in combination.

[0121] The thickness of the protective film is typically 1–100 μm, and from the viewpoint of strength and operability, it is preferably 5–60 μm, more preferably 10–55 μm, and even more preferably 15–50 μm.

[0122] The protective film can simultaneously possess other optical functions, and can also be formed in a laminated structure with multiple layers. From the viewpoint of optical properties, a thin protective film is preferred; however, if it is too thin, its strength decreases, resulting in a film with poor processability. A suitable film thickness is 5–100 μm, preferably 10–80 μm, and more preferably 15–70 μm.

[0123] The protective film can be made of cellulose acylated film, polycarbonate resin, cyclic olefin resin such as norbornene, (meth)acrylic polymer film, polyester resin such as polyethylene terephthalate, etc. When the polarizing element has protective films on both sides, and when bonding them using a water-based adhesive such as PVA adhesive, from the perspective of moisture permeability, it is preferable that at least one side of the protective film is either a cellulose acylated film or a (meth)acrylic polymer film, with a cellulose acylated film being preferred.

[0124] The first protective film and the second protective film may be the same or different. Both the first and second protective films may have a surface treatment layer (coating layer) such as an antistatic layer on their outer surface (the surface opposite to the polarizing element). It should be noted that the thickness of the first and second protective films includes the thickness of the surface treatment layer.

[0125] As the first protective film, in order to meet the above requirement (ii), a film with a temperature of 40°C, a relative humidity of 90%, and a permeability of 20 g / m² can be used. 2 Protective film for temperatures below 100°C. The moisture permeability of the protective film can be adjusted by using different materials and thicknesses. A permeability of 20 g / m³ is achieved at 40°C and 90% relative humidity. 2 For protective films used for days or less, cyclic olefin resin films and films with water vapor shielding layers laminated in a dry manner are preferred.

[0126] As a protective film for at least one purpose, it may have a phase difference function for purposes such as viewing angle compensation. In this case, the film itself may have a phase difference function, or it may have a separate phase difference layer, or it may be a combination of both.

[0127] It should be noted that the film with phase difference function can also be composed of an additional protective film sandwiched between the polarization element and bonded together via an adhesive layer or bonding agent layer.

[0128] <Adhesive Layer>

[0129] In optical laminates, bonding layers are used to bond the layers together. Examples of bonding layers include adhesive layers or bonding layers.

[0130] (Adhesive layer)

[0131] The adhesive layer can be used, for example, to bond the protective film to the polarizing element. The adhesive constituting the adhesive layer can be any suitable adhesive. Water-based adhesives, solvent-based adhesives, and active energy radiation-cured adhesives can be used, but water-based adhesives are preferred.

[0132] The thickness of the adhesive coating can be set to any suitable value. For example, it can be set so that an adhesive layer with a desired thickness is obtained after curing or heating (drying). The thickness of the adhesive layer is preferably 0.01 μm or more and 7 μm or less, more preferably 0.01 μm or more and 5 μm or less, further preferably 0.01 μm or more and 2 μm or less, and most preferably 0.01 μm or more and 1 μm or less.

[0133] (Water-based adhesive)

[0134] As a water-based adhesive, any suitable water-based adhesive can be used. Among these, a water-based adhesive containing PVA-based resin (PVA-based adhesive) is preferred. From an adhesive properties perspective, the average degree of polymerization of the PVA-based resin contained in the water-based adhesive is preferably around 100 to 5500, more preferably 1000 to 4500. From an adhesive properties perspective, the average degree of saponification is preferably around 85 mol% to 100 mol%, more preferably 90 mol% to 100 mol%.

[0135] As the PVA-based resin contained in the aforementioned water-based adhesive, a resin containing acetyl groups is preferred because the PVA-based resin layer exhibits excellent adhesion and durability to the protective film. The PVA-based resin containing acetyl groups can be obtained, for example, by reacting a PVA-based resin with a diene using an optional method. The degree of acetyl group modification in the PVA-based resin containing acetyl groups is typically 0.1 mol% or more, preferably around 0.1 mol% to 20 mol%.

[0136] The resin concentration of the above-mentioned water-based adhesive is preferably 0.1% to 15% by mass, more preferably 0.5% to 10% by mass.

[0137] Water-based adhesives can also contain crosslinking agents. Known crosslinking agents can be used as crosslinking agents. Examples include water-soluble epoxy compounds, dialdehydes, and isocyanates.

[0138] When the PVA resin is a PVA resin containing acetyl groups, the crosslinking agent is preferably any one of glyoxal, glyoxylate, or hydroxymethyl melamine, more preferably any one of glyoxal or glyoxylate, and particularly preferably glyoxal.

[0139] Aqueous adhesives may also contain organic solvents. From the perspective of miscibility with water, alcohols are preferred organic solvents, with methanol or ethanol being more preferred. Some urea-based compounds have low solubility relative to water but sufficient solubility relative to alcohols. In this case, dissolving the urea-based compound in an alcohol to prepare an alcoholic solution of the urea-based compound, and then adding the alcoholic solution of the urea-based compound to an aqueous PVA solution to prepare the adhesive, is also a preferred method.

[0140] The methanol concentration in the aqueous adhesive is preferably 10% by mass or more and 70% by mass or less, more preferably 15% by mass or more and 60% by mass or less, and even more preferably 20% by mass or more and 60% by mass or less. By keeping the methanol concentration at 10% by mass or more, it is easier to further suppress polyolefin formation under high-temperature conditions. In addition, by keeping the methanol content at 70% by mass or less, color deterioration can be suppressed.

[0141] (Active energy radiation curing adhesive)

[0142] Reactive energy radiation-cured adhesives are adhesives that cure upon exposure to reactive energy radiation such as ultraviolet rays. Examples include adhesives containing polymerizable compounds and photopolymerization initiators, adhesives containing photoreactive resins, and adhesive resins containing photoreactive crosslinking agents. Examples of polymerizable compounds include photopolymerizable monomers such as photocurable epoxy monomers, photocurable acrylic monomers, and photocurable urethane monomers, as well as oligomers derived from these monomers. Examples of photopolymerization initiators include compounds containing substances that generate reactive species such as neutral free radicals, anionic free radicals, and cationic free radicals upon exposure to reactive energy radiation such as ultraviolet rays.

[0143] (Adhesive layer)

[0144] An adhesive layer can be used, for example, for bonding the antireflective film to the first protective film.

[0145] The adhesive layer can be constructed using an adhesive composition with resins such as (meth)acrylic resins, rubber resins, urethane resins, ester resins, silicone resins, and polyvinyl ether resins as the main component. Among these, adhesive compositions with (meth)acrylic resins as the base polymer are particularly suitable due to their excellent transparency, weather resistance, and heat resistance. The adhesive composition can be either radioactively cured or thermosetting. The thickness of the adhesive layer is typically 3–30 μm, preferably 3–25 μm.

[0146] The (meth)acrylic resin (base polymer) used as a component of the adhesive can, for example, be a polymer or copolymer with one or more (meth)acrylates such as butyl (meth)acrylate, ethyl (meth)acrylate, isooctyl (meth)acrylate, or 2-ethylhexyl (meth)acrylate as monomers. It is preferable to copolymerize polar monomers in the base polymer. Examples of polar monomers include, for example, (meth)acrylic acid, 2-hydroxypropyl (meth)acrylate, hydroxyethyl (meth)acrylate, (meth)acrylamide, N,N-dimethylaminoethyl (meth)acrylate, and glycidyl (meth)acrylate, monomers having carboxyl, hydroxyl, amide, amino, or epoxy groups, such as those found in (meth)acrylic acid, 2-hydroxypropyl (meth)acrylate, hydroxyethyl (meth)acrylate, methacrylamide, N,N-dimethylaminoethyl (meth)acrylate, and glycidyl (meth)acrylate.

[0147] The adhesive composition may contain only the aforementioned base polymer, but it typically also contains a crosslinking agent. Examples of crosslinking agents include: metal ions with a valence of divalent or higher that form a metal carboxylate salt between themselves and a carboxyl group; polyamine compounds that form an amide bond between themselves and a carboxyl group; polyepoxide compounds and polyols that form an ester bond between themselves and a carboxyl group; and polyisocyanate compounds that form an amide bond between themselves and a carboxyl group. Among these, polyisocyanate compounds are preferred.

[0148] The energy storage modulus of the adhesive layer is preferably 0.001 to 0.350 MPa at a frequency of 1 Hz and a temperature of 23°C, more preferably 0.001 to 0.200 MPa, even more preferably 0.001 to 0.180 MPa, and particularly preferably 0.010 to 0.170 MPa.

[0149] The thickness of the adhesive layer is preferably 1 to 200 μm, more preferably 2 to 100 μm, even more preferably 2 to 80 μm, and particularly preferably 3 to 50 μm.

[0150] In this invention, by using an anti-reflective film formed by sputtering in each layer as described above, a highly scratch-resistant optical laminate can be constructed.

[0151] In this case, by controlling the energy storage modulus of the adhesive layer used in bonding the antireflective film to the first protective film and the thickness of the adhesive layer to the following ranges, an optical laminate with high indentation hardness (represented by pencil hardness) and resistance to breakage of the antireflective layer can be formed, which is therefore particularly preferred.

[0152] Specifically, when the storage modulus of the adhesive layer is measured according to the method described in the embodiments below, it is preferably 0.050 to 0.170 MPa, more preferably 0.080 to 0.170 MPa, even more preferably 0.100 to 0.170 MPa, and particularly preferably 0.120 to 0.160 MPa.

[0153] The thickness of the adhesive layer is preferably 3 to 30 μm, more preferably 3 to 20 μm, even more preferably 3 to 10 μm, and particularly preferably 3 to 8 μm.

[0154] [Manufacturing method of optical laminates]

[0155] The method for manufacturing an optical laminate according to this embodiment includes a moisture content adjustment step and an anti-reflective film lamination step. In the moisture content adjustment step, when manufacturing an optical laminate having feature (a), the moisture content of the polarizing element is adjusted such that it is above the equilibrium moisture content of 30% relative humidity at 20°C and below the equilibrium moisture content of 48% relative humidity at 20°C. The method for adjusting the moisture content of the polarizing element is as described above. In the moisture content adjustment step, when manufacturing an optical laminate having feature (b), the moisture content of the optical laminate is adjusted such that it is above the equilibrium moisture content of 30% relative humidity at 20°C and below the equilibrium moisture content of 48% relative humidity at 20°C. The method for adjusting the moisture content of the optical laminate is as described above. In the anti-reflective film lamination step, a polarizing element and an anti-reflective film are laminated. The order of the moisture content adjustment process and the anti-reflective film lamination process is not limited, and the moisture content adjustment process and the anti-reflective film lamination process can also be performed in parallel. The method for manufacturing the optical laminate of this embodiment may also include a protective film lamination process of laminating the polarizing element and the protective film.

[0156] [Display device]

[0157] The aforementioned optical laminate can be used in various display devices such as liquid crystal display devices and organic EL display devices. Display devices using the optical laminate of this embodiment can be formed with excellent resistance to damp heat and high temperatures. Because of its excellent resistance to damp heat and high temperatures, the display device using the optical laminate of this embodiment can be appropriately used as a display device for automotive applications.

[0158] As a display device, it includes a display unit and an optical laminate stacked on the viewable side surface of the display unit. The optical laminate is stacked on the viewable side surface of the display unit in such a way that a polarizing element and an anti-reflective film are arranged sequentially from the display unit side. In the stacking of the display unit and the optical laminate, for example, the adhesive layer described above is used.

[0159] <Display Unit>

[0160] Examples of display units include liquid crystal cells (LCDs) and organic EL cells (OLEDs). As a liquid crystal cell, any of the following can be used: a reflective liquid crystal cell utilizing external light, a transmissive liquid crystal cell utilizing light from a light source such as a backlight, or a semi-transmissive / semi-reflective liquid crystal cell utilizing both external light and light from a light source. When the liquid crystal cell utilizes light from a light source, the display device (liquid crystal display device) also provides a polarizing plate on the side of the display cell (liquid crystal cell) opposite to the viewable side, and further provides a light source. The polarizing plate on the light source side is preferably bonded to the liquid crystal cell via a suitable adhesive layer. As for the driving method of the liquid crystal cell, various driving methods can be used, such as VA mode, IPS mode, TN mode, STN mode, and curved orientation (π-type).

[0161] As an organic EL unit, an organic EL unit in which a transparent electrode, an organic light-emitting layer, and a metal electrode are sequentially stacked on a transparent substrate to form a light emitter (organic electroluminescent emitter) can be appropriately used. The organic light-emitting layer is a stack of various organic thin films, such as a stack of a hole injection layer containing a triphenylamine derivative and a light-emitting layer containing a fluorescent organic solid such as anthracene, a stack of these light-emitting layers and an electron injection layer containing a perylene derivative, or a stack of a hole injection layer, a light-emitting layer, and an electron injection layer, etc.

[0162] Example

[0163] The present invention will be further described in detail below with reference to examples; however, the present invention is not limited to these examples. In the examples, parts and percentages representing content or usage are used as quality standards unless otherwise specified. It should be noted that the determination of various physical properties in the following examples is performed using the methods described below.

[0164] [Determination Method]

[0165] (1) Methods for measuring film thickness

[0166] Measurements were taken using the MH-15M digital micrometer manufactured by Nikon Corporation.

[0167] (2) Moisture permeability of the anti-reflective film

[0168] According to Appendix B of JISK 7129:2008, the humidity permeability of the antireflective film was measured in an atmosphere with a temperature of 40°C and a relative humidity of 90%.

[0169] (3) Determination of the thickness of each layer of the anti-reflective layer

[0170] Measurements were taken using a reflective spectrophotometer FE3000 manufactured by Otsuka Electronics Co., Ltd.

[0171] (4) Energy storage modulus

[0172] The storage modulus G' of the adhesive layer is determined according to (I) to (III) below.

[0173] (I) Take two samples, each 25±1mg, from the adhesive layer and shape them into approximately spherical shapes.

[0174] (II) The obtained approximately spherical sample is attached to the upper and lower surfaces of the type I fixture, and then clamped together with the upper and lower surfaces using the type L fixture. The sample is configured as follows: type L fixture / adhesive layer / type I fixture / adhesive layer / type L fixture.

[0175] (III) The storage modulus G' of the sample prepared as described was determined using the dynamic viscoelasticity measuring device "DVA-220" manufactured by IT Measurement Control Co., Ltd. at a temperature of 23°C, a frequency of 1Hz, and an initial strain of 1N.

[0176] (A) Fabrication of polarization elements

[0177] A 75 μm thick polyvinyl alcohol (PVA) film, formed from PVA with an average degree of polymerization of approximately 2400 and a saponification degree of 99.9 mol% or higher, was uniaxially stretched to approximately 5 times its original length using a dry method. While maintaining tension, it was then immersed in pure water at 60°C for 1 minute, followed by immersion in an aqueous solution of iodine / potassium iodide / water at a weight ratio of 0.05 / 5 / 100 at 28°C for 60 seconds. Subsequently, it was immersed in an aqueous solution of potassium iodide / boric acid / water at a weight ratio of 8.5 / 8.5 / 100 at 72°C for 300 seconds. Finally, after washing with pure water at 26°C for 20 seconds, it was dried at 65°C to obtain a 28 μm thick polarizing element with iodine adsorbed and oriented in the PVA.

[0178] (B) Preparation of adhesive

[0179] 50g of a modified PVA resin containing acetyl groups (Mitsubishi Chemical Co., Ltd.: GOHSENX Z-410) was dissolved in 950g of pure water, heated at 90°C for 2 hours, and then cooled to room temperature to obtain PVA solution A.

[0180] PVA-based adhesive 1 was prepared by combining PVA solution A, maleic acid, glyoxal, and pure water in such a manner that each compound was in the concentrations described below.

[0181] PVA concentration 3.0% by weight

[0182] 0.01% by weight of maleic acid

[0183] Glyoxal 0.15% by weight

[0184] (C) Saponification of cellulose acylate membranes

[0185] A commercially available cellulose acylated membrane TD40 (manufactured by Fujifilm Corporation: 40 μm thickness) was immersed in a 1.5 mol / L NaOH aqueous solution (saponification solution) maintained at 55°C for 2 minutes, followed by washing with water. Then, it was immersed in a 0.05 mol / L sulfuric acid aqueous solution at 25°C for 30 seconds, and then washed with running water for 30 seconds to neutralize the membrane. Afterward, water was removed three times using an air knife, and the membrane was dried in a drying zone at 70°C for 15 seconds to produce a saponified membrane.

[0186] (D) Fabrication of optical laminates

[0187] (Fabrication of polarizing plate 1)

[0188] On both sides of the previously obtained polarizing element, the thickness of the dried adhesive layer is adjusted to 100 nm on both sides using a PVA-based adhesive 1. After laminating the saponified cellulose acylated film prepared above using a roller laminator, the film is dried at 80°C for 5 minutes to obtain the polarizing plate 1.

[0189] (Determination of equilibrium moisture content)

[0190] The polarizing plate 1 obtained above was stored at 20°C and relative humidity of 30%, 35%, 40%, 45%, or 50% for 72 hours. The moisture content was then determined using the Karl Fischer method after 66, 69, and 72 hours of storage. Under any humidity conditions, the moisture content remained unchanged after 66, 69, and 72 hours of storage. Therefore, the moisture content of polarizing plate 1 can be considered to be the same as the equilibrium moisture content of the storage environment. When the moisture content of the polarizing plate reaches equilibrium under a certain storage temperature, the moisture content of the polarizing elements in the polarizing plate can also be considered to have reached equilibrium under that storage temperature. Furthermore, when the moisture content of the polarizing elements in the polarizing plate reaches equilibrium under a certain storage environment, the moisture content of the polarizing plate can also be considered to have reached equilibrium under that storage environment.

[0191] The moisture content of the polarizer 1 obtained above, immediately after drying, was determined using the Karl Fischer method and compared with the equilibrium moisture content mentioned above. This moisture content was equivalent to that at 20°C and 30% relative humidity. For polarizer 1, to ensure it matched the equilibrium moisture content at 20°C and 30% relative humidity, it was stored at 20°C and 30% relative humidity for 72 hours.

[0192] (Preparation of polarizing plates 2-5)

[0193] For polarizing plate 1, the drying temperature or time was varied to make the moisture content the same as the equilibrium moisture content recorded in Table 1, and then it was stored for 72 hours at a temperature of 20°C and a relative humidity of 35%, 40%, 45%, or 50%.

[0194] (E) Fabrication of anti-reflective film

[0195] (Preparation of anti-glare hard coating)

[0196] 50 parts by weight of UV-curable urethane acrylate monomers (refractive index 1.51), 50 parts by weight of UV-curable acrylate monomers (refractive index 1.51), 14 parts by weight of methyl methacrylate-styrene copolymer beads (refractive index 1.55) with an average particle size of 3.5 μm, 5 parts by weight of benzophenone-based photopolymerization initiator, and toluene were mixed. The resulting solution (40% by weight solids) was coated onto a 40 μm thick triacetylcellulose film (refractive index 1.49) and dried at 120°C for 5 minutes. Subsequently, it was cured using UV irradiation to form an anti-glare hard coating with a surface texture of approximately 4 μm thickness. The arithmetic mean roughness Ra of this anti-glare hard coating is 0.43 nm.

[0197] (Preparation of a transparent hard coating)

[0198] 50 parts by weight of UV-curable urethane acrylate monomer (refractive index 1.51), 50 parts by weight of UV-curable acrylate monomer (refractive index 1.51), 5 parts by weight of benzophenone-based photopolymerization initiator, and toluene were mixed. The resulting solution (40% by weight solids) was coated onto a 40 μm thick triacetylcellulose film (refractive index 1.49) and dried at 120°C for 5 minutes. Subsequently, it was cured using UV irradiation to form a transparent hard coating with a flat surface and a thickness of approximately 4 μm, thus creating a transparent hard coating film. The arithmetic mean roughness Ra of this transparent hard coating is 0.03 nm.

[0199] (Fabrication of anti-reflective film 1)

[0200] According to the embodiment disclosed in Japanese Patent Application Publication No. 2019-035969, the aforementioned anti-glare hard coating film is introduced into a roll-to-roll sputtering film forming apparatus. While the film is being moved, the surface on which the anti-glare hard coating is formed is subjected to bombardment treatment (using Ar gas plasma treatment), and a 5nm SiO layer is formed as an adhesion enhancement layer. xA layer (x < 2) is formed, upon which a 20 nm Nb₂O₅ layer, a 35 nm SiO₂ layer, another 35 nm Nb₂O₅ layer, and a 100 nm SiO₂ layer are sequentially formed to create a 4-layer antireflective layer with a thickness of 190 nm. A fluorine-based resin is then formed on the antireflective layer to achieve a thickness of 5 nm as an antifouling layer, thus producing antireflective film 1. The moisture permeability of antireflective film 1 under conditions of 40°C and 90% relative humidity is 5 g / m². 2 ·sky.

[0201] (Making of anti-reflective films 2 and 3)

[0202] Based on the embodiments disclosed in Japanese Patent Application Publication No. 2017-227898, and with modifications to the film-forming conditions, antireflective films 2 and 3 were manufactured, exhibiting different moisture permeability than antireflective film 1. The moisture permeability of antireflective films 2 and 3 at a temperature of 40°C and a relative humidity of 90% were 10 g / m³, respectively. 2 · Tianhe 60g / m 2 ·sky.

[0203] (Fabrication of anti-reflective film 4)

[0204] Except for the use of a transparent hard coating instead of an anti-glare hard coating, an anti-reflective film 4 is manufactured in the same manner as anti-reflective film 1. The anti-reflective film 4 has a moisture permeability of 5 g / m² under conditions of 40°C and 90% relative humidity. 2 ·sky.

[0205] (Production of anti-reflective film 5)

[0206] Except for replacing the sputtering method of the anti-reflective layer with a coating method, and making the anti-reflective layer structure as shown below, the anti-reflective film 5 is manufactured in the same manner as the anti-reflective film 1. The anti-reflective film 5 has a moisture permeability of 300 g / m² under conditions of 40°C and 90% relative humidity. 2 ·sky.

[0207] Referring to Japanese Patent Application Publication No. 2004-126220, paragraph

[0105] , the anti-reflective layer is defined as an anti-reflective layer consisting of the following three layers.

[0208] The first layer is the refractive index layer (refractive index: 1.63, film thickness: 67nm).

[0209] Second high-refractive-index layer (refractive index: 1.90, film thickness: 107 nm)

[0210] The third low-refractive-index layer (refractive index: 1.43, film thickness: 86 nm)

[0211] (F) Preparation of adhesive layer

[0212] Adhesive layer A: A commercially available sheet of acrylic adhesive with a release agent, consisting of 38μm PET, is applied to both sides. The adhesive layer has a thickness of 5μm and a storage modulus of 0.14MPa.

[0213] Adhesive layer B: A commercially available sheet of acrylic adhesive with a release agent, consisting of 38μm PET, is applied to both sides. The adhesive layer has a thickness of 25μm and a storage modulus of 0.06MPa.

[0214] [Example 1]

[0215] The antireflective film 1 fabricated above has an adhesive layer A on the surface without the laminated antireflective layer. It should be noted that corona treatment was applied to the bonding surfaces of each material during the bonding process.

[0216] The optical laminate of Example 1 is fabricated by laminating an antireflective film 1 onto one side of the polarizing plate 1 prepared above with adhesive layer A, and then laminating an adhesive layer B onto the other side. It should be noted that corona treatment was applied to the bonding surfaces of each material during the bonding process. The resulting optical laminate is composed of layers of "antireflective film 1 / adhesive layer A / polarizing plate 1 / adhesive layer B / PET with release agent".

[0217] For the resulting optical laminate, in order to have the same moisture content as the polarizer used to constitute the optical laminate, the moisture content of the optical laminate was adjusted by storing it for 72 hours under the same conditions as storing the polarizer for 72 hours. Since the optical laminate was also stored for 72 hours, it can be considered that equilibrium was reached under this storage environment. Similarly, the moisture content of the polarizer and polarizing elements in the optical laminate can also be considered to have reached equilibrium under this storage environment. Furthermore, when the moisture content of the polarizer or polarizing elements in the optical laminate reaches equilibrium under a certain storage environment, the moisture content of the optical laminate can also be considered to have reached equilibrium under that storage environment.

[0218] [Examples 2-6 and Comparative Examples 1-3]

[0219] Compared to the optical laminate of Example 1, except that the polarizing plate and antireflective film described in Table 1 were used as the polarizing plate and antireflective film, the optical laminates of Examples 2 to 6 and Comparative Examples 1 to 3 were made in the same manner as Example 1. In order to have the same moisture content as the polarizing plate used later, the moisture content of the optical laminate was adjusted by storing it for 72 hours under the same conditions as storing the polarizing plate for 72 hours.

[0220] [evaluate]

[0221] (Reflected glare)

[0222] The resulting optical laminate was cut into 200mm × 200mm pieces and bonded to a 300mm × 300mm thick alkali-free glass plate with a thickness of 0.7mm via adhesive layer B. Adhesive layer B was then laminated onto a polarizing plate 1, cut into 200mm × 200mm pieces. On the side of the alkali-free glass not bonded to the optical laminate, the polarizing plate 1 was bonded to it via adhesive layer B in such a manner that the absorption axes of the polarizing plates were orthogonal Nicol prisms, thus creating an evaluation sample.

[0223] The evaluation sample prepared above was placed on the observation stage with the antireflective film visible. A tabletop fluorescent lamp was shone at an angle, and the reflected glare was evaluated relative to the shimmering direction using the following criteria in the mirror direction. The evaluation results are shown in Table 1.

[0224] A: No reflected glare from the fluorescent lamps can be observed at all.

[0225] B: The reflected glare from the fluorescent lamps is basically not observable.

[0226] C: Slight glare from the fluorescent lamp can be observed.

[0227] D: The reflected glare from the fluorescent lamp can be clearly observed.

[0228] (Scratch resistance)

[0229] Nippon Steel Wool Bonster #0000 was fixed to a scratch testing machine, a load of 2000g was applied, and 10 back-and-forth scratch tests were performed. The appearance of the antireflective film surface after the test was visually confirmed. Samples without visible scratches were designated "A", and samples with visible scratches were designated "D". The evaluation results are shown in Table 1.

[0230] (Damp heat durability test)

[0231] The optical laminates prepared above were cut into 35mm × 35mm pieces, the release film was removed, and they were bonded to 50mm × 50mm, 1mm thick glass plates to create evaluation samples. These evaluation samples were then subjected to a temperature of 50℃ and a pressure of 5kgf / cm². 2 After autoclaving at 490.3 kPa for 1 hour, the plates were placed in an environment of 23°C and 55% relative humidity for 24 hours. Subsequently, the degree of polarization (initial value) was measured. After storage at 85°C and 85% relative humidity for 500 hours, the degree of polarization was measured again. For the degree of polarization, a V7100 oscilloscope manufactured by Nippon Spectrophotometer Co., Ltd. was used to measure the transmittance (Tp) when the absorption axes of the two polarizing plates were overlapped parallel to each other and the transmittance (Tc') when the absorption axes were overlapped orthogonally. The degree of polarization (P) was calculated using the following formula.

[0232] Degree of polarization P = ((Tp - Tc') / (Tp + Tc')) 0.5 ×100[%]

[0233] In addition, the change in degree of polarization can be calculated using the following formula.

[0234] The change in polarization degree ΔP = (polarization degree (initial value)) - (polarization degree after storage)

[0235] Based on the changes in polarization degree mentioned above, an evaluation was conducted using the following criteria. The evaluation results are presented in Table 1.

[0236] A: The change in polarization degree ΔP is less than 0.01%.

[0237] B: The change in polarization degree ΔP is greater than 0.01% and less than 0.02%.

[0238] C: The change in polarization degree ΔP is greater than 0.02% and less than 0.05%.

[0239] D: The change in polarization degree ΔP is greater than 0.05%.

[0240] (High-temperature durability test)

[0241] The optical laminates of Examples 1-6 and Comparative Examples 1-3 prepared above were cut into 50mm × 100mm pieces, the release film was removed, and the surface of adhesive layer B was bonded to alkali-free glass (trade name "EAGLE XG", manufactured by Corning Corporation) to produce evaluation samples. These evaluation samples were then subjected to a temperature of 50°C and a pressure of 5 kgf / cm². 2 After autoclaving at (490.3 kPa) for 1 hour, the sample was placed in an environment of 23°C and 55% relative humidity for 24 hours. Subsequently, the transmittance (initial value) was measured, and the sample was stored at 95°C for 240–960 hours, with transmittance measured every 240 hours. The following criteria were used for evaluation based on the time it took for the transmittance to decrease by more than 5% relative to the initial value. The results are shown in Table 1.

[0242] A: The decrease in transmittance after 960 hours is less than 5%.

[0243] B: The transmittance decreases by more than 5% after 720 hours or 960 hours.

[0244] C: The transmittance decreases by more than 5% after 480 hours.

[0245] D: The transmittance decreases by more than 5% after 240 hours.

[0246] Table 1

[0247]

Claims

1. A display device comprising a display unit and an optical laminate, The optical laminate includes a polarizing element, an anti-reflective film, a protective film laminated on the surface of the polarizing element next to the anti-reflective film, and an adhesive layer for bonding the anti-reflective film and the protective film. The optical laminate is stacked on the visible side surface of the display unit in such a manner that the polarizing element and the anti-reflective film are arranged sequentially from the display unit side. The moisture content of the polarizing element is above the equilibrium moisture content at 20°C and 20% relative humidity, and below the equilibrium moisture content at 20°C and 35% relative humidity. The antireflective film has a temperature of 40℃, a relative humidity of 90%, and a moisture permeability of 10g / m³. 2 Below the sky, The adhesive layer has a storage modulus of 0.050 MPa to 0.170 MPa and a thickness of 3 μm to 30 μm. The anti-reflective film comprises a substrate film and an anti-reflective layer disposed on the surface of the substrate film. The antireflective layer comprises multiple thin films with different refractive indices. The antireflective layer comprises a thin film with silicon dioxide (SiO2) as the main component. The antireflective layer comprises a thin film with niobium pentoxide (Nb₂O₅) or titanium dioxide (TiO₂) as the main components.

2. A display device comprising a display unit and an optical laminate, The optical laminate includes a polarizing element, an anti-reflective film, a protective film laminated on the surface of the polarizing element next to the anti-reflective film, and an adhesive layer for bonding the anti-reflective film and the protective film. The optical laminate is stacked on the visible side surface of the display unit in such a manner that the polarizing element and the anti-reflective film are arranged sequentially from the display unit side. The moisture content of the optical laminate is above the equilibrium moisture content at 20°C and 20% relative humidity, and below the equilibrium moisture content at 20°C and 35% relative humidity. The antireflective film has a temperature of 40℃, a relative humidity of 90%, and a moisture permeability of 10 g / m³. 2 Below the sky, The adhesive layer has a storage modulus of 0.050 MPa to 0.170 MPa and a thickness of 3 μm to 30 μm. The anti-reflective film comprises a substrate film and an anti-reflective layer disposed on the surface of the substrate film. The antireflective layer comprises multiple thin films with different refractive indices. The antireflective layer comprises a thin film with silicon dioxide (SiO2) as the main component. The antireflective layer comprises a thin film with niobium pentoxide (Nb₂O₅) or titanium dioxide (TiO₂) as the main components.

3. The display device according to claim 1 or 2, wherein, The thickness of the protective film is 10μm to 55μm.

4. The display device according to claim 1 or 2, wherein, The thickness of the anti-reflective layer is 100nm to 350nm.

5. The display device according to claim 1 or 2, wherein, The antireflective film also has a hard coating layer disposed between the substrate film and the antireflective layer.

6. A method for manufacturing an optical laminate, which is the method for manufacturing the optical laminate according to claim 1. The manufacturing method includes a moisture content adjustment step, which adjusts the moisture content of the polarizing element to a level above the equilibrium moisture content of 20°C and 20% relative humidity and below the equilibrium moisture content of 35% relative humidity at 20°C.

7. A method for manufacturing an optical laminate, which is the method for manufacturing the optical laminate according to claim 2. The manufacturing method includes a moisture content adjustment step, which adjusts the moisture content of the optical laminate to a level above the equilibrium moisture content of 20°C and 20% relative humidity and below the equilibrium moisture content of 35% relative humidity at 20°C.

Citation Information

Patent Citations

  • Manufacture of sealed type lead storage battery

    JP1993046064B2

  • How to duplicate holograms

    JP1994085103B2

  • Production of low reflection laminated body

    JP1994186401A

  • Optical antireflection member, its production and cathode ray tube

    JP1997080205A

  • Antireflection material and polarizing film using the same

    JP2000187102A